Prejudicial appearances the logic of American antidiscrimination law - Post, Robert 1947- (Duke University Press, 2012)
Prejudicial appearances: the logic of American antidiscrimination law / Robert C. Post -- Stereotypes and the shaping of identity / Anthony Appiah -- "Appearances aside" / Judith Butler -- Cover blindness / Thomas C. Grey -- Discrimination in the eyes of the law: how "color blindness" discourse disrupts and rationalizes social stratification / Reva B. Siegel -- Response to commentators / Robert C. Post